"Plate-anchor" shaped POSS-functionalized graphene oxide with self-fixing effect in polyimide matrix: Molecular dynamic simulations and experimental analysis. (26th May 2019) - Yuan, Rui; Ji, Li; Wu, Yanping; Li, Hongxuan; Ju, Pengfei; Chen, Lei; Zhou, Huidi; Chen, Jianmin
Abstract: In this paper, we report an approach for synthesizing "plate-anchor" shaped polyhedral oligomeric silsesquioxane (POSS)-functionalized graphene oxide nanosheets with self-fixing effect via the amide formation. The resultant POSS-GO hybrid has excellent dispersibility in various organic solvents, such as N, N′-dimethylacetamide, pyridine, tetrahydrofuran and carbon tetrachloride. The molecular dynamics simulation (MD) indicates that the POSS-GO nanocomposites can not only react with PI resin by amidation, but also can be self-fixed in the resin through the "plate-anchor" structure, in which the GO nanosheet acts as "plate", the POSS is considered as the "anchor", thus being highly attractive for reinforcing polymer matrix. As expected, only 0.3 wt % addition of POSS-GO into polyimide (PI) can significantly increase the mechanical strength, thermal stability and friction and wear properties of polymer matrix. It is envisioned that the "plate-anchor" shaped composite exhibits outstanding advantages in the field of advanced materials.